Etiological classification of high sedimentation rate and relation with other inflammatory markers - Sultan Gozde Temiz; Baris Sagcan; Helin Tantekin; Kadem Arslan (Medicine Science)
This study describes the causes of significantly increased erythrocyte sedimentation rate (ESR) and compares the etiological categories based on inflammatory markers. We collected data from the patients who applied between March 2020 and August 2023. Patients were categorized into five groups based on their identified etiology. Categories were sorted as infection, inflammatory, malignancy, renal, and others. Inflammation markers were compared between groups and ROC analysis was performed if there was a significant difference. The cause of the elevated ESR levels in 291 patients was determined. The median age was 58 (18-92). ESR levels were lower in females (113, 106-120) than in males (119, 109-120) (p=0.015). The distribution of etiological disease categories was as follows: inflammatory (41.9%), infection (35.1%), malignancy (18.2%), renal (3.1%), and others (1.7%). Albumin levels were lower in the malignancy group than in the inflammatory group (p [Med-Science 2024; 13(4.000): 788-95]